Efficient technology of basalt fiber-reinforced concrete for use in monolithic construction - Akramov Khusnitdin; Yusupov Rakhimbay; Ergashov Jasurbek (E3S Web of Conferences, 2023)
The development and production of basalt fiber-reinforced concrete have been carried out on a large scale recently, driven by the efficiency of using basalt fibers as a micro-reinforcing additive in cement-based concretes. For the successful application of basalt fiber-reinforced concrete in monolithic construction, there must be an accessible and efficient technology for commonly used concrete compositions. This paper presents the results of an analysis of foreign literature sources, which conclude that new experimental research is needed to improve the compositions and technology of basalt fiber-reinforced concrete using local construction materials. The article provides the results of such research and recommendations for an efficient basalt fiber-reinforced concrete technology.The conducted research has shown that introducing basalt fiber into the composition of heavy concrete according to the proposed technology contributes to a 15% increase in compressive strength compared to similar concrete without micro-reinforcement. Additionally, it is possible to save up to 10% or more on cement consumption.